Biomaterials Regulating Bone Hematoma for Osteogenesis. Issue 23 (21st July 2020) - Yang, Ying; Xiao, Yin
Abstract: Blood coagulation in tissue healing not only prevents blood loss, but also forms a natural scaffold for tissue repair and regeneration. As blood clot formation is the initial and foremost phase upon bone injury, and the quality of blood clot (hematoma) orchestrates the following inflammatory and cellular processes as well as the subsequent callus formation and bone remodeling process. Inspired by the natural healing hematoma, tissue‐engineered biomimic scaffold/hydrogels and blood prefabrication strategies attract significant interests in developing functional bone substitutes. The alteration of the fracture hematoma ca significantly accelerate or impair the overall bone healing process. This review summarizes the impact of biomaterials on blood coagulation and provides evidence on fibrin network structure, growth factors, and biomolecules that contribute to bone healing within the hematoma. The aim is to provide insights into the development of novel implant and bone biomaterials for enhanced osteogenesis. Advances in the understanding of biomaterial characteristics (e.g., morphology, chemistry, wettability, and protein adsorption) and their effect on hematoma properties are highlighted. Emphasizing the importance of the initial healing phase of the hematoma endows the design of advanced biomaterials with the desired regulatory properties for optimal coagulation and hematoma properties, thereby facilitating enhanced osteogenesis and ideal therapeutic effects. Abstract : The importance of hematoma formation during osteogenesis is reviewed and the effect of biomaterials on blood coagulation, fibrin network structures, growth factor release, and stem cell recruitment is highlighted. The paper points to the future development of functional bone biomaterials targeting hematoma and early bone healing process for osteogenesis.